Supporting Ukraine Militarily: Why Is the West Divided? - Vesa Kanniainen; Juha-Matti Lehtonen (CESifo GmbH, 2025)
Following Russia's attack on Ukraine on February 24, 2022, Western countries have been providing military assistance to Ukraine. However, relative to GDP, the support from the small Baltic and Nordic countries has been greater than that of the larger European NATO countries. This article introduces first an alliance model to examine the incentive for alliance member countries to invest in their own national security in a deterrence equilibrium with no warfare. It is shown that an underinvestment incentive arises. The Russian invasion to Ukraine changed the rules of the game. Therefore, the article offers an explanation for the distribution of Ukrainian military assistance based on the national security classification of European NATO member states in a two-stage game-theoretic model. This distribution turns out to be conditional on the expectations associated with the second stage of the war game if Russia wins the war in its first stage and if there is uncertainty about NATO's ability to commit to its Article 5 to provide security to all of its members.
Keywords: D72; D74; H56; 330; military aid to Ukraine; alliance theory; NATO; two-stage game